Acquisition of aspect and aktionsart by children in Croatian and French - Martinot, Claire; Andel, Maja; Kumar, Sunil (ZAS Papers in Linguistics, 2003)
Our results indicate some differences in the use of aspect between French and Croatian speaking children. In Croatian language children always manage to keep the appropriate aspect, unlike French children. However, the imperfective aspect seems to be better acquired in French children than the perfective aspect. The perfective aspect, the marked form both in French as well as in Croatian, is related to the lexical meaning of the verbs. The acquisition of the Aktionsart in both languages seems to be more a matter of semantics than of morphology. Furthermore, our data suggest the existence of a specific developmental trend in the use of Aktionsart (intensive, iterative and inchoative), which is similar for children speaking Slavic and Romanic languages.